PENGARUH KIM SEON HO SEBAGAI BRAND AMBASSADOR TERHADAP KEPUTUSAN PEMBELIAN EVERWHITE - Edo Fernando Susilo; Azalia Gerungan; Pierre Mauritz Sundah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
The growth of the skin care industry which continues to experience rapid development is because women generally want to appear physically beautiful and youthful, it becomes a primary need and a big target for the beauty cosmetic industry. Increasing growth creates large opportunities for companies and requires them to implement different strategies, one of which is using brand ambassadors. Everwhite, is the first local skin care product to collaborate with South Korean celebrity Kim Seon Ho as its brand ambassador. This study uses an explanatory quantitative method with the aim of knowing and measuring how much brand ambassador has an impact on consumers in making purchasing decisions. Data was collected through online questionnaires from 100 respondents with the results of the calculation of the Slovin formula with a precision level of 10%. The statistical data analysis technique in measuring the effect is the test of determination. The results showed that Kim Seon Ho as a brand ambassador was able to influence 78.7% of Everwhite's purchasing decisions. This confirms the assumptions of the Value Expectacy theory significantly.